Currency crises, speculative attacks and financial instability in a global world: A Post Keynesian approach with reference to Brazilian currency crisis - Antonio J. A; Fernando Ferrari; Luiz Fernando de Paula (Universidad Central de Venezuela, 2004)
This paper develops a critical view of the conventional currency crisis models and presents a Post Keynesian view on financial instability and speculative attack. It also analyzes the 1998/1999 Brazilian currency crisis, according to the Post Keynesian approach.